Preparation method of absorbable composite material for interface screw and interface screw
Through multi-stage feed blending technology, the materials are processed in the twin-screw extruder, which solves the problems of difficulty in injection molding and demolding of interface screw materials and the high biosafety risks, and achieves good dispersion of the materials and improves injection molding performance.
Patent Information
- Application Number
- CN202411678039.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing interface screw materials are difficult to release during injection molding and require intermittent coating of mold release agents, which affects production efficiency and product quality. At the same time, the biosafety risk of polylactic acid/HA composites is high.
Using multi-stage feeding blending technology, a specific premix is added to the main feeding port and two side feeding ports of the double-side feeding twin-screw extruder to improve the nano-scale hydroxyapatite powder. Dispersion uniformity in polylactic acid matrix simplifies material formulation components, reduces biosafety risks, and improves injection molding and mold release.
The good dispersion and injection molding performance of polylactic acid/HA composite materials are achieved, and the mold release agent coating is eliminated, the production efficiency and product quality are improved, while the biosafety risks of the material are reduced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical composite materials, and in particular to a preparation method of an absorbable composite material for an interface screw and the interface screw. Background Art
[0002] Interference screws are commonly used implants in sports medicine orthopedic surgery. They are suitable for reattaching ligaments, tendons, soft tissues and bones during knee cruciate ligament reconstruction surgery. Currently, most of the interface screws approved for clinical use are metal screws and polyetheretherketone (PEEK) screws, both of which have good mechanical strength, can provide sufficient support during the healing period of patients' bones and ligaments, and have very good auxiliary treatment effects. However, metal screws are prone to damage ligaments and other soft tissues and must be removed from the patient's body through a secondary operation after healing, which not only causes secondary trauma to the patient but also increases the patient's economic burden; PEEK cannot be degraded, which is not conducive to tissue regeneration at the site of injury. It has become a development trend to replace traditional non-absorbable materials with bioresorbable materials.
[0003] Polylactic acid is a biodegradable polymer material that is safe for the human body and friendly to the environment. It can be used to make medical sutures, injectable microcapsules, degradable bone nails, implants, artificial bones, artificial skin, etc. It has the characteristics of good biocompatibility, no need for secondary surgery to remove it after surgery, non-toxic metabolites, and ultimately converted into carbon dioxide and water in the body. However, it has low strength, low binding ability with bones, and no osteoconductivity. After being implanted in the human body, the acidic products generated by degradation are prone to cause aseptic inflammatory reactions and even lead to aseptic bone tissue necrosis. Hydroxyapatite (HA) is a bioceramic similar to human bones and teeth. It has good biological activity and osteoconductivity. HA is weakly alkaline, which can reduce the aseptic inflammatory reaction caused by the acidic products generated by the degradation of polylactic acid. The composite material obtained by blending HA with polylactic acid can combine the advantages of the two materials and has good biocompatibility, biological activity and mechanical properties when used as an interface screw.
[0004] However, HA, especially nano HA powder, has a high surface energy. When blended with polylactic acid, it has poor dispersibility in the polylactic acid matrix and is prone to agglomeration. Moreover, HA is a hydrophilic inorganic material, and the compatibility between HA and polylactic acid is poor, and the interfacial bonding force is weak, resulting in cracks at the interface between the two phases of the composite material, affecting the mechanical properties of the polylactic acid / HA composite material. For this reason, in the process of preparing polylactic acid / HA composite materials, HA is usually surface modified, or a compatibilizer such as maleic anhydride is introduced to improve the dispersibility of HA in the polylactic acid matrix or improve the interfacial bonding force between polylactic acid and HA, thereby achieving the purpose of obtaining a polylactic acid / HA composite material with ideal mechanical properties. For example, patent document CN103387756B discloses a modification method and application of hydroxyapatite, specifically: first disperse hydroxyapatite in N,N-dimethylformamide, then add citric acid, heat and stir at 100-120°C for reaction, after the reaction is complete, filter, wash and dry to obtain citric acid-treated hydroxyapatite; then, under the protection of inert gas, add the obtained citric acid-treated hydroxyapatite to xylene, ultrasonically disperse for 20-60 minutes, add a xylene solution of lactide and a stannous octoate catalyst in sequence, heat to 120-140°C and stir for grafting reaction, after the reaction is complete, cool to room temperature, wash and dry to obtain modified hydroxyapatite; then, add the obtained modified hydroxyapatite to a polylactic acid material in an amount of 1%-25% by mass for compounding to obtain a polylactic acid / hydroxyapatite composite material with high flexural strength, which can be used to develop various new fracture internal fixation materials such as bone plates, bone nails, and bone blocks. Patent document CN106421928A discloses a hydroxyapatite / poly-L-lactic acid composite material that can be degraded in the human body, wherein stearic acid is used to modify hydroxyapatite powder: hydroxyapatite powder is added to anhydrous ethanol, and ultrasonic dispersion is performed to obtain a hydroxyapatite suspension with a concentration of 10wt%; stearic acid is added to anhydrous ethanol to prepare a stearic acid solution with a concentration of 10wt%; then the hydroxyapatite suspension and the stearic acid solution are mixed in a mass ratio of 1: (1-3), heated and stirred to allow stearic acid and hydroxyapatite to fully react, filtered, and vacuum dried to obtain modified hydroxyapatite powder. Patent document CN111671981A discloses a method for preparing an absorbable composite material for an interface screw sheath, wherein the absorbable composite material is composed of hydroxyapatite, PEG, maleic anhydride, and polylactic acid materials, and the connection between HA, PEG, and polylactic acid materials is achieved by introducing maleic anhydride and adjusting the amount of maleic anhydride to enhance the interfacial compatibility of HA and polylactic acid.Whether it is surface modification of nano-hydroxyapatite or addition of compatibilizer, the components of the polylactic acid / HA composite material will increase. As a medical implant material, the more components the material has, especially the more components that have not been issued as medical implant material standards, the more uncertain its potential toxicity and biosafety risks will be. When applying for product registration, a full set of biological evaluation test data must be provided, which significantly increases the R&D cost and the R&D cycle.
[0005] In addition, due to the low thermal shrinkage of polylactic acid materials, such as the thermal shrinkage of left-handed polylactic acid (PLLA) is only about 0.3%, there is a strong adhesion between the polylactic acid material and the mold during the injection molding process, which makes demolding difficult; in addition, the interface screw surface has an external thread structure. When the interface screw is injection molded with polylactic acid composite materials, the contact area between the thread and the mold increases, further increasing the difficulty of demolding. Most of the current countermeasures are to intermittently apply silicone oil release agents on the mold surface. Although this solves the demolding problem, it greatly reduces the injection molding production efficiency and increases the labor cost. A small amount of release agent will remain on the surface of the interface screw, affecting product quality. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing an absorbable composite material for an interface screw and an interface screw, so as to simplify the formula components of the polylactic acid-based composite material, reduce the biological safety risks of the material, and give the polylactic acid-based composite material good injection molding demolding properties, so as to eliminate the process of intermittently coating the mold surface with a release agent when injection molding the interface screw.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing an absorbable composite material for an interface screw, wherein the absorbable composite material is composed of 60% to 80% of polylactic acid, 10% to 30% of polylactic acid-glycolic acid copolymer, 5% to 10% of polyethylene glycol and 5% to 20% of hydroxyapatite powder by weight percentage, and the method for preparing the absorbable composite material comprises the following steps:
[0009] S1, adding a premix 1 prepared by mixing polylactic acid, part of polyethylene glycol and part of hydroxyapatite to the main feeding port of a double-side feeding twin-screw extruder;
[0010] S2, adding premix 2 prepared by mixing polylactic acid-glycolic acid copolymer, part of polyethylene glycol and part of hydroxyapatite to the first side feeding port;
[0011] S3, adding a premix 3 formed by mixing part of polyethylene glycol and part of hydroxyapatite to the second side feed port, and melt-extruding at a temperature of 180-220° C. in a twin-screw extruder, cooling with water, and pelletizing to obtain the product;
[0012] The weight ratio of hydroxyapatite added in steps S1, S2 and S3 is (1-3): (1-4): 1; the weight ratio of polyethylene glycol added in steps S1, S2 and S3 is (2-4): (1-3): 1.
[0013] The second side feeding port is located at the rear section of the first side feeding port, the first side feeding port is 2 to 4 heating cylinder sections away from the main feeding port, and the second side feeding port is 1 to 3 heating cylinder sections away from the first side feeding port.
[0014] The average particle size of the hydroxyapatite is 200-750 nm.
[0015] The inventors of the present invention unexpectedly discovered through a large number of experimental investigations that by utilizing a multi-stage feeding and blending technology, specific premixes are respectively added to the main feeding port and two side feeding ports of a double-side feeding twin-screw extruder, and through multiple dispersions and mixing, the dispersion uniformity of nano-hydroxyapatite powder in a polylactic acid matrix can be improved without modifying hydroxyapatite and without adding compatibilizers such as maleic anhydride, and the injection molding demolding properties of polylactic acid / hydroxyapatite composite materials can be improved.
[0016] The polylactic acid is L-polylactic acid having an intrinsic viscosity of 1.5-4.0 dL / g at 25° C.; and or the molecular weight of the polyethylene glycol is 600-5000, preferably 1000-3000, and more preferably 1000-2000.
[0017] The molar proportion of the lactide structure in the polylactic acid-glycolic acid copolymer is 70-90%, and the molar proportion of the glycolide structure is 10-30%; the intrinsic viscosity of the polylactic acid-glycolic acid copolymer at 25° C. is 1.0-3.0 dL / g.
[0018] Preferably, the usage ratio of the polylactic acid to the polylactic acid-glycolic acid copolymer is (4-6):1, and the polylactic acid is a L-polylactic acid having an intrinsic viscosity of 2.0-3.5 dL / g at 25°C.
[0019] Preferably, the molar ratio of the lactide structure to the glycolide structure in the polylactic acid-glycolic acid copolymer is 90:10 or 75:25, and the intrinsic viscosity of the polylactic acid-glycolic acid copolymer at 25° C. is 1.4-2.5 dL / g.
[0020] Preferably, the shell of the twin-screw extruder comprises 9 sections of heating barrels connected end to end, the main feeding port is arranged at the first section of the heating barrel, the first side feeding port is 3 to 4 sections of the heating barrel away from the main feeding port, and the second side feeding port is 2 to 3 sections of the heating barrel away from the first side feeding port; the weight ratio of hydroxyapatite added in steps S1, S2 and S3 is 2:3:1, and the weight ratio of polyethylene glycol added in steps S1, S2 and S3 is 3:2:1.
[0021] Preferably, the melt extrusion process parameters are: the processing temperatures of zones 1-9 are set to 170-180°C, 175-185°C, 180-190°C, 190-200°C, 190-200°C, 200~210°C, 210-220°C, 200~210°C, 200~210°C, the die temperature is 200~210°C, and the main screw speed is 200-250r / min.
[0022] Another object of the present invention is to provide an interface screw prepared by injection molding of the absorbable composite material prepared by the above preparation method.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] 1) The preparation method of the absorbable composite material for interface screws of the present invention improves the uniformity of nano-HA dispersion in the polylactic acid / HA composite material by optimizing the premixing method of material components and adopting a multi-stage feeding and blending technology, and unexpectedly improves the processing performance of the polylactic acid / HA composite material. The process of intermittently coating the mold surface with a release agent during injection molding of the interface screw can omit the process, which can greatly improve the injection molding production efficiency of the interface screw and reduce the manual operation cost.
[0025] 2) The method provided by the present invention is used to prepare the polylactic acid / HA composite material, which can simplify the formula components of the polylactic acid / HA composite material. The composite material only contains polylactic acid, polylactic acid-glycolic acid copolymer, polyethylene glycol (drug excipient) and hydroxyapatite components with good biocompatibility, all of which have issued medical implant material standards. It is used as an interface screw implanted in a bone tunnel, which has a lower biosafety risk.
[0026] 3) The polylactic acid / HA composite injection-molded interface screw prepared by the method of the present invention does not need to be coated with a silicone oil release agent on the surface of the injection mold, and there is no risk of contaminating the product during the injection molding process, and the quality of the injection molded product is higher. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0028] The raw materials used in the embodiments of the present invention are as follows:
[0029] PLLA-1: intrinsic viscosity is 1.50~2.00dL / g, purchased from Jinan Daigang Bioengineering Co., Ltd., model number is DG-L-200;
[0030] PLLA-2: intrinsic viscosity 2.0-2.5 dL / g, purchased from Jinan Daigang Bioengineering Co., Ltd., model DG-LH250;
[0031] PLLA-3: intrinsic viscosity 2.5-3.0 dL / g, purchased from Jinan Daigang Bioengineering Co., Ltd., model DG-LOH300;
[0032] PLGA (75:25)-1: intrinsic viscosity 1.0-1.4 dL / g, purchased from Changchun Hanggai Biotechnology Co., Ltd., model PLG75-12;
[0033] PLGA (75:25)-2: intrinsic viscosity 1.8-2.2 dL / g, purchased from Shenzhen Boli Biomaterials Co., Ltd., model PLG75-22;
[0034] PLGA (90:10)-1: intrinsic viscosity 2.2-2.5 dL / g, purchased from Dongguan Haosheng Plastic Raw Materials Co., Ltd., model PLG90-24;
[0035] PLGA (90:10)-2: intrinsic viscosity 1.4-1.8 dL / g, purchased from Dongguan Haosheng Plastic Raw Materials Co., Ltd., model PLG90-18;
[0036] PEG-1000: purchased from Yisheng Biotechnology (Shanghai) Co., Ltd.;
[0037] PEG-1500: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0038] Nano-hydroxyapatite: average particle size 500 nm, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0039] Example 1
[0040] (1) By weight, 65 parts of PLLA-2, 3.5 parts of PEG1000 and 2.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 20 parts of PLGA (90:10)-2, 1.75 parts of PEG1000 and 2.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.75 parts of PEG1000 and 2.66 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0041] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0042] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 2 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0043] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0044] Example 2
[0045] (1) By weight, 65 parts of PLLA-2, 5 parts of PEG1000 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 10 parts of PLGA (75:25)-2, 3.3 parts of PEG1000 and 7.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.7 parts of PEG1000 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0046] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0047] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 2 sections of the heating cylinder away from the first side feeding port.
[0048] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0049] Example 3
[0050] (1) By weight, 60 parts of PLLA-2, 5 parts of PEG1000 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 15 parts of PLGA (75:25)-2, 3.3 parts of PEG1000 and 7.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.7 parts of PEG1000 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0051] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0052] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 2 sections of the heating cylinder away from the first side feeding port.
[0053] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0054] Example 4
[0055] (1) By weight, 63 parts of PLLA-2, 5 parts of PEG1000 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 12 parts of PLGA (75:25)-2, 3.3 parts of PEG1000 and 7.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.7 parts of PEG1000 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0056] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0057] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 2 sections of the heating cylinder away from the first side feeding port.
[0058] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0059] Example 5
[0060] (1) By weight, 64 parts of PLLA-2, 5 parts of PEG1000 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 11 parts of PLGA (75:25)-2, 3.3 parts of PEG1000 and 7.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.7 parts of PEG1000 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0061] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0062] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 2 sections of the heating cylinder away from the first side feeding port.
[0063] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0064] Example 6
[0065] (1) By weight, 70 parts of PLLA-3, 2.67 parts of PEG1500 and 3.75 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 12 parts of PLGA (90:10)-2, 4 parts of PEG1500 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.33 parts of PEG1500 and 1.25 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0066] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0067] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0068] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0069] Example 7
[0070] (1) By weight, 65 parts of PLLA-3, 2.67 parts of PEG1500 and 3.75 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 17 parts of PLGA (90:10)-2, 4 parts of PEG1500 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.33 parts of PEG1500 and 1.25 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0071] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0072] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0073] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0074] Example 8
[0075] (1) By weight, 66 parts of PLLA-3, 2.67 parts of PEG1500 and 3.75 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 16 parts of PLGA (90:10)-2, 4 parts of PEG1500 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.33 parts of PEG1500 and 1.25 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0076] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0077] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0078] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0079] Example 9
[0080] (1) By weight, 71 parts of PLLA-3, 2.67 parts of PEG1500 and 3.75 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 11 parts of PLGA (90:10)-2, 4 parts of PEG1500 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.33 parts of PEG1500 and 1.25 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0081] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0082] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0083] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0084] Example 10
[0085] (1) By weight, 75 parts of PLLA-1, 2.5 parts of PEG1500 and 1.875 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 15 parts of PLGA (90:10)-1, 1.25 parts of PEG1500 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.25 parts of PEG1500 and 0.625 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0086] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0087] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0088] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0089] Embodiment 11
[0090] (1) By weight, 60 parts of PLLA-3, 6.67 parts of PEG1000 and 10 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 10 parts of PLGA (75:25)-1, 1.67 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.66 parts of PEG1000 and 3.33 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0091] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0092] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 3 sections of the heating cylinder away from the first side feeding port.
[0093] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0094] Example 12
[0095] (1) By weight, 80 parts of PLLA-1, 3.43 parts of PEG1500 and 4.28 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 12 parts of PLGA (75:25)-1, 3.43 parts of PEG1000 and 4.28 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.14 parts of PEG1500 and 1.44 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0096] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0097] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 2 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 1 section of the heating cylinder away from the first side feeding port.
[0098] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0099] Example 13
[0100] (1) By weight, 60 parts of PLLA-1, 2.5 parts of PEG1500 and 1.875 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 30 parts of PLGA (90:10)-1, 1.875 parts of PEG1500 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 0.625 parts of PEG1500 and 0.625 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0101] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0102] Wherein, in step (2), the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 2 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 1 section of the heating cylinder away from the first side feeding port.
[0103] In step (2), the temperature of each zone of the twin-screw extruder is: zone 1 170~180°C, zone 2 175~185°C, zone 3 180~190°C, zone 4 190~200°C, zone 5 190~200°C, zone 6 200~210°C, zone 7 210~220°C, zone 8 200~210°C, zone 9 200~210°C, die head temperature 200~210°C, and main screw speed 200~250r / min.
[0104] Embodiment 14
[0105] According to weight, 60 parts of PLLA-2, 15 parts of PLGA (75:25)-2, 10 parts of PEG1000 and 15 parts of nano-hydroxyapatite are weighed, mixed evenly and added from the main feeding port of a twin-screw extruder, melt-extruded at a temperature of 180-220° C. in the twin-screw extruder, water-cooled and pelletized to obtain an absorbable composite material for interface screws.
[0106] Among them, the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, and the temperature of each zone of the twin-screw extruder is: 170~180℃ in zone 1, 175~185℃ in zone 2, 180~190℃ in zone 3, 190~200℃ in zone 4, 190~200℃ in zone 5, 200~210℃ in zone 6, 210~220℃ in zone 7, 200~210℃ in zone 8, 200~210℃ in zone 9, the head temperature is 200~210℃, and the main screw speed is 200~250r / min.
[0107] Embodiment 15
[0108] According to weight, 60 parts of PLLA-2, 15 parts of PLGA (75:25) -2 and 10 parts of PEG1000 are weighed, mixed evenly and added from the main feeding port of the twin-screw extruder, and 15 parts of nano-hydroxyapatite are added from the first side feeding port of the twin-screw extruder, so that all materials entering the two feeding ports are mixed evenly in the twin-screw extruder, the temperature of the extruder is controlled at 180-220°C, extrusion, cooling, and pelletizing are performed, and an absorbable composite material for interface screws is obtained.
[0109] Among them, the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, and the first side feeding port is 3 sections of heating cylinders away from the main feeding port; the temperature of each zone of the twin-screw extruder is: 170~180℃ in zone 1, 175~185℃ in zone 2, 180~190℃ in zone 3, 190~200℃ in zone 4, 190~200℃ in zone 5, 200~210℃ in zone 6, 210~220℃ in zone 7, 200~210℃ in zone 8, 200~210℃ in zone 9, the head temperature is 200~210℃, and the main screw speed is 200~250r / min.
[0110] Example 16
[0111] (1) By weight, 60 parts of PLLA-2, 3.33 parts of PEG1000 and 5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 15 parts of PLGA (75:25)-2, 3.34 parts of PEG1000 and 7.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 3.33 parts of PEG1000 and 2.5 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0112] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0113] Among them, the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of heating cylinders away from the main feeding port, and the second side feeding port is 2 sections of heating cylinders away from the first side feeding port; the temperature of each zone of the twin-screw extruder is: 170~180℃ in zone 1, 175~185℃ in zone 2, 180~190℃ in zone 3, 190~200℃ in zone 4, 190~200℃ in zone 5, 200~210℃ in zone 6, 210~220℃ in zone 7, 200~210℃ in zone 8, 200~210℃ in zone 9, the head temperature is 200~210℃, and the main screw speed is 200~250r / min.
[0114] Embodiment 17
[0115] (1) By weight, 60 parts of PLLA-2, 5 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 15 parts of PLGA (75:25)-2, 3.34 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.67 parts of PEG1000 and 1.66 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0116] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0117] Among them, the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of heating cylinders away from the main feeding port, and the second side feeding port is 2 sections of heating cylinders away from the first side feeding port; the temperature of each zone of the twin-screw extruder is: 170~180℃ in zone 1, 175~185℃ in zone 2, 180~190℃ in zone 3, 190~200℃ in zone 4, 190~200℃ in zone 5, 200~210℃ in zone 6, 210~220℃ in zone 7, 200~210℃ in zone 8, 200~210℃ in zone 9, the head temperature is 200~210℃, and the main screw speed is 200~250r / min.
[0118] Embodiment 18
[0119] (1) By weight, 60 parts of PLLA-2, 5 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 15 parts of PLGA (75:25)-2, 3.34 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.67 parts of PEG1000 and 1.66 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0120] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0121] Among them, the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 5 sections of heating cylinders away from the main feeding port, and the second side feeding port is 2 sections of heating cylinders away from the first side feeding port; the temperature of each zone of the twin-screw extruder is: 170~180℃ in zone one, 175~185℃ in zone two, 180~190℃ in zone three, 190~200℃ in zone four, 190~200℃ in zone five, 200~210℃ in zone six, 210~220℃ in zone seven, 200~210℃ in zone eight, 200~210℃ in zone nine, the head temperature is 200~210℃, and the main screw speed is 200~250r / min.
[0122] Embodiment 19
[0123] (1) By weight, 60 parts of PLLA-2, 5 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 1; 15 parts of PLGA (75:25)-2, 3.34 parts of PEG1000 and 6.67 parts of nano-hydroxyapatite were mixed evenly to obtain premix 2; 1.67 parts of PEG1000 and 1.66 parts of nano-hydroxyapatite were mixed evenly to obtain premix 3;
[0124] (2) The premix 1 obtained in step (1) is added from the main feed port of the twin-screw extruder, the premix 2 is added from the first side feed port, and the premix 3 is added from the second side feed port, so that all the materials entering the three feed ports are mixed evenly in the twin-screw extruder. The temperature of the extruder is controlled at 180-220°C, and the extruder is extruded, cooled, and pelletized to obtain an absorbable composite material for interface screws.
[0125] Among them, the shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 4 sections of the heating cylinder away from the first side feeding port; the temperature of each zone of the twin-screw extruder is: 170~180℃ in zone 1, 175~185℃ in zone 2, 180~190℃ in zone 3, 190~200℃ in zone 4, 190~200℃ in zone 5, 200~210℃ in zone 6, 210~220℃ in zone 7, 200~210℃ in zone 8, 200~210℃ in zone 9, the head temperature is 200~210℃, and the main screw speed is 200~250r / min.
[0126] Performance testing:
[0127] The relevant performance tests were carried out according to the following methods. The test results are shown in Tables 1 and 2.
[0128] 1. Demolding effect: The absorbable composite materials prepared in Examples 1 to 19 were respectively subjected to injection molding of interface screws. The demolding performance was divided into the following four levels according to the time required for complete demolding: (1) poor - mold sticking; (2) medium - manual assisted demolding; (3) good - basically able to demold automatically, occasionally requiring manual assistance; (4) excellent - completely automatic demolding. Injection molding process parameters: injection molding temperature of 210°C; injection pressure of 240 bar; holding time of 40 s; mold temperature of 35°C.
[0129] 2. Axial pull-out force of interface screw: Test according to the method specified in YY / T1504.
[0130] Table 1
[0131]
[0132] Table 2
[0133]
[0134] Ten injection-molded interface screws of Example 3 and Examples 14 and 15 were randomly selected, and the axial pull-out force test was performed according to the above-mentioned axial pull-out force test method. The corresponding axial pull-out force data were recorded, and the average value and range were calculated. The test results are shown in Table 3.
[0135] Table 3 Axial pull-out force stability test results
[0136]
[0137] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an absorbable composite material for an interface screw, characterized in that: The absorbable composite material is composed of 60% to 80% of polylactic acid, 10% to 30% of polylactic acid-glycolic acid copolymer, 5% to 10% of polyethylene glycol and 5% to 20% of hydroxyapatite powder by weight percentage. The preparation method of the absorbable composite material comprises the following steps: S1, adding a premix 1 prepared by mixing polylactic acid, part of polyethylene glycol and part of hydroxyapatite to the main feeding port of a double-side feeding twin-screw extruder; S2, adding premix 2 prepared by mixing polylactic acid-glycolic acid copolymer, part of polyethylene glycol and part of hydroxyapatite to the first side feeding port; S3, adding a premix 3 formed by mixing part of polyethylene glycol and part of hydroxyapatite to the second side feed port, and melt-extruding at a temperature of 180-220° C. in a twin-screw extruder, cooling with water, and pelletizing to obtain the product; The weight ratio of hydroxyapatite added in steps S1, S2 and S3 is (1-3): (1-4): 1; the weight ratio of polyethylene glycol added in steps S1, S2 and S3 is (2-4): (1-3):
1.
2. The preparation method according to claim 1, characterized in that: The second side feeding port is located at the rear section of the first side feeding port, the first side feeding port is 2 to 4 heating cylinder sections away from the main feeding port, and the second side feeding port is 1 to 3 heating cylinder sections away from the first side feeding port.
3. The preparation method according to claim 1, characterized in that: The average particle size of the hydroxyapatite is 200-750 nm.
4. The preparation method according to claim 1, characterized in that: The polylactic acid is L-polylactic acid having an intrinsic viscosity of 1.5-4.0 dL / g at 25° C.; and / or the molecular weight of the polyethylene glycol is 600-5000.
5. The preparation method according to claim 1, characterized in that: The molar proportion of the lactide structure in the polylactic acid-glycolic acid copolymer is 70-90%, and the molar proportion of the glycolide structure is 10-30%; the intrinsic viscosity of the polylactic acid-glycolic acid copolymer at 25° C. is 1.0-3.0 dL / g.
6. The preparation method according to claim 5, characterized in that: The dosage ratio of the polylactic acid to the polylactic acid-glycolic acid copolymer is (4-6):1, and the polylactic acid is a left-handed polylactic acid with a characteristic viscosity of 2.0-3.5 dL / g.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the lactide structure to the glycolide structure in the polylactic acid-glycolic acid copolymer is 90:10 or 75:25, and the intrinsic viscosity of the polylactic acid-glycolic acid copolymer at 25° C. is 1.5-2.5 dL / g.
8. The preparation method according to claim 2, characterized in that: The shell of the twin-screw extruder includes 9 sections of heating cylinders connected end to end, the main feeding port is arranged at the first section of the heating cylinder, the first side feeding port is 3 to 4 sections of the heating cylinder away from the main feeding port, and the second side feeding port is 2 to 3 sections of the heating cylinder away from the first side feeding port; the weight ratio of hydroxyapatite added in the steps S1, S2 and S3 is 2:3:1, and the weight ratio of polyethylene glycol added in the steps S1, S2 and S3 is 3:2:
1.
9. The preparation method according to claim 8, characterized in that: The melt extrusion process parameters are as follows: the processing temperatures of zones 1 to 9 are set to 170~180℃, 175~185℃, 180~190℃, 190~200℃, 190~200℃, 200~210℃, 210~220℃, 200~210℃, 200~210℃, the die temperature is 200~210℃, and the main screw speed is 200~250r / min.
10. An interface screw, characterized in that: The interface screw is obtained by injection molding of the absorbable composite material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Modification method and application of hydroxyapatite
CN103387756B
Hydroxyapatite / polylactic acid composite material degradable in human bodies and method for preparing hydroxyapatite / polylactic acid composite material
CN106421928A
Absorbable composite material for interface screw sheath and preparation method thereof
CN111671981A
Preparation method of hydroxyapatite composite biomaterial
CN106943622A
Absorbable interface screw
CN118755249A